2009
DOI: 10.1007/s00103-009-0787-7
|View full text |Cite
|
Sign up to set email alerts
|

Stand, Möglichkeiten und Grenzen der Telemedizin in Deutschland

Abstract: In Germany there are many successful special applications of telemedicine. However, these projects are generally not extendable to the whole nation because of the highly complex German health care system, limited funding, heterogeneous IT standards in ambulatory and hospital care, insufficient official electronic health card use, the different data protection and privacy regulations of the federal and state governments, doubts of physicians and patients as well as unequal costs and benefits for the various per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Many patients believe that TM disrupts the relationship with their physician and fosters social isolation. 72,76,81 It is reported that people worry about being neglected by their physician and about data confidentiality. 70,82 Furthermore, patients might perceive TM as an intrusion into their privacy and reject the medicalisation of their home.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many patients believe that TM disrupts the relationship with their physician and fosters social isolation. 72,76,81 It is reported that people worry about being neglected by their physician and about data confidentiality. 70,82 Furthermore, patients might perceive TM as an intrusion into their privacy and reject the medicalisation of their home.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the limited scalability is caused by incompatibility with existing IT systems. 81 Efforts at standardisation vary considerably between German states. While some states have invested €10 million in defining supra-regional standards, others remain passive.…”
Section: Discussionmentioning
confidence: 99%
“…14,53,54 It is not possible to directly relate the trends observed in Poland to what has been happening in other countries. [55][56][57] Based on the almost constant increase in the global number of similar publications indexed in PubMed (from 366 papers indexed in the year 1995 to 2946 papers indexed in the year 2015), the contribution of the activity of Polish authors may be considered lower than expected for a country of this size and population. The current review may help other researchers with similar telecommunication and healthcare infrastructures.…”
Section: Discussionmentioning
confidence: 99%
“…The technologies range from standard telephone audio consultations [ 2 ] to virtual reality scenarios [ 3 , 4 ] and even drones [ 5 ]. Though these technologies have been available for some time, telehealth has not been widely used in German healthcare for legal, technical, and organizational reasons [ 6 ].…”
Section: Introductionmentioning
confidence: 99%